Santri Anti Baper: the Development of Narratives of Religious Moderation Through Digital Workshop in the Margoyoso Pati Pesantren Community - A Dimyati; Kamilia Hamidah; Siti Asiyah Asiyah; Sri Naharin (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
This dedication is a community-based service that aims to equip and boost the capacity of ‘santri’ in producing alternative narratives of religious moderation to the fight against intolerant narratives on social media. Kajen Margoyoso Pati Town is a village with tens of thousands of ‘santri’ potentially dominate digital public with religious moderation narratives. The team used the Asset Based Community Development (ABCD) methodology to empower participants in this session, namely, human resource assets, social assets, and infrastructure assets are among the assets owned by pesantren. ‘Santri’ were still passive consumers of digital content and lack the awareness to produce digital content. Expected result from this training, learners will be able to generate alternative narratives by transforming negative narratives into positive narratives to counterbalance the narrative of intolerance on social media. From this training, students who participated in this training will implement on their pesantren web pages and on social media.